Numerical simulation and analysis of fluid flow hydrodynamics through a structured array of circular cylinders forming porous medium - Kundu, Partha; Kumar, Vimal; Hoarau, Yannick; Mishra, Indra Mani (Applied mathematical modelling, 2016)
•Spatially periodic infinite array of circular cylinders modeled as a porous medium.•3D and 2D pore-flow structure was investigated using LES and RANS simulations.•The TKE and TDR increased with ReD.•The TKE and TDR increase with a decrease in porosity.•The macroscopic pressure gradient was investigated for a wide range of ϕ and ReD. Numerical analysis of the mechanisms that govern the flow in a porous region is crucial for modeling porous media flows. This study describes an adapted and efficient turbulence modeling technique for this category of porous media flows. The main objective of the present study is to provide a detailed pore scale description of fluid flow and to analyze the formation of coherent structures in the wake region close to the solid wall subject to the effects of fine-scale turbulence. The computations were performed in a three-dimensional representative elementary volume (REV) of a porous matrix, which comprised a periodic array of circular cylinders. Two flow-modeling strategies were employed: the steady Reynolds averaged Navier–Stokes (RANS) and transient large eddy simulation (LES) approaches. In the RANS modeling framework, both standard k–ε and low Re k–ε turbulence models were used. The porosity (ϕ) of the porous REV and Reynolds number (ReD) varied from 0.3 to 0.8 and 10 to 40,000, respectively. We investigated the effects of porosity and ReD on the pore scale velocity distribution, overall macroscopic pressure gradient, and turbulent dynamics, and performed comparisons using RANS and LES calculations within the porous REV. The Darcy parameter (i.e., medium permeability, K) was computed and a correlation was determined between the medium porosity and permeability. The macroscopic pressure gradients in the three-dimensional REV were also compared with the Kozeny–Carman and Darcy–Forchheimer law.